Utilização da radiação síncroton no estudo in situ da deformação criogênica de metais CFC - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
The mechanical behavior of metals depends on the strain process and the characteristics of the material, in particular its crystalline structure and stacking fault energy (SFE). The objective of this work is the study of the influence of the cryogenic strain compared to the room temperature (RT) and the strain rate the mechanical properties of aluminum, copper and silver, by means of a thermomechanical system (XTMS station installed at CNPEM National Center for Energy and Materials Research - Campinas - Brazil) which considers X-ray diffraction during deformation by tensile test.. The results showed that the cryogenic temperature has an increase of the strength and ductility simultaneously, having a more significant increase of elongation in the higher strain rate. It also shows an increase in microstrain and decrease in the mean crystallite size causing an increase in discordance density, which suggests a partial suppression in dynamic recovery at low temperature. The refinement that is presented is higher at cryogenic temperature manifesting with a smaller size of dimples in the surfaces of fracture.
Keywords: Deformação Criogênica; Energia de falha de empilhamento; Taxa de deformação; Estrutura cristalina; Radiação Síncrotron; Difração de Raios X in situ; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA